Laloo Prasad, an apostle of social justice - Ashrafī, Vahāb. (Educational Pub. House, 1994)
On Laloo Prasad Yadav, Chief Minister of Bihar, India.
Includes bibliographical references (p. 126-127).
On Laloo Prasad Yadav, Chief Minister of Bihar, India.